Die Windverbreitung im Gebiet des Mt. Fuji - Yoshimura, Minoru (ERDKUNDE, 1971)
The surface wind conditions in the Mt. Fuji region were analysed using the results from field investigations of the wind shaped larches and wind data obtained at the climatological stations in this area. The following points are made clear. 1) In summer, two different directions of prevailing wind are seen. One is W or NW observed at the top of Mt. Fuji and the other is a southerly wind at the slope below 2000 m which changes its direction according to the direction of slope. 2) In winter, three different wind directions are seen. They are NW or WNW at the top of the mountain, SW between 2000 m and 2500 m which changes its direction to NW at the southern slope and to S at the western slope, and the northerly wind at the climatological stations at the foot of the mountain. 3) Monthly mean wind velocity at 2500 m in July and January which is estimated by the equation (I) is strong enough to deform the tree.